2014
DOI: 10.1007/978-3-319-06749-0_12
|View full text |Cite
|
Sign up to set email alerts
|

Towards Electronic Identification and Trusted Services for Biometric Authenticated Transactions in the Single Euro Payments Area

Abstract: Abstract. On 14th October 2013 the European Parliament Committee on Industry, Research and Energy (ITRE) paved the way on the regulation and harmonisation for electronic identification, authentication and trust services (eIDAS) between EU member states. This upcoming regulation will ensure mutual recognition and acceptance of electronic identification across borders, which also provides an opportunity to establish trusted electronic transactions in the Single Euro Payments Area (SEPA). The contribution of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In this work, we have presented a concrete approach on the protection of multimodal biometric templates, underlying critical privacy issues, while focusing on the suggestions for future research. Multimodal biometric systems are mostly discussed for the impact of their use on publicly accepted, reliable identification systems [31], [53], overcoming the obstacles of uni-modal ones.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we have presented a concrete approach on the protection of multimodal biometric templates, underlying critical privacy issues, while focusing on the suggestions for future research. Multimodal biometric systems are mostly discussed for the impact of their use on publicly accepted, reliable identification systems [31], [53], overcoming the obstacles of uni-modal ones.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The conducted tests demonstrate advantages, while introducing new tasks. The evaluation of a complete biometric system is a complex issue and requires stronger user involvement for feature level schemes [31]. Compact multibiometric templates need to be generated, offering, in this way, an improved concrete content of information.…”
Section: Multibiometric System Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [29,30] investigated fields such as e-banking, analyzing current threats and the adaption of the eIDAS standard towards trusted banking transactions. Specifically, the work of [30] extended the eIDAS definition to biometrically authenticated transactions. The authors identified eIDAS as highly suitable for banking transactions due to its security protocols and infrastructure.…”
Section: Related Workmentioning
confidence: 99%